Specific methods for the analysis of starch from underground starchy crops - Cereda, Marney Pascoli [UNESP]; Ávila, Bianca; Bet, Camila Delinski; Silveira Junior, Jose Francisco Santos; Leal Cortes, Paloma Freire Neves (Elsevier, 2022)
Information regarding many crops that store starch in underground organs, especially the type of starch that they produce, is still poorly known. A thorough analysis of the composition of these starches is warranted to further study and establish their potentials. Proximal analysis can provide an overview, which highlights the most important components. The selection of the analysis methods gives credibility to the results and favor the use of these starches by researchers and industries. The South American industries rarely follow official methods. On the other hand, official methods do not always consider the specific characteristics of tropical starches. With this focus, this chapter provides an overview of the official methods available in the literature and fills the gap with the methods used in industry. The selected methods cover the three most important sectors for starch applications: textiles, paper, as well as paperboard and foodstuffs.
Keywords: industrial analyses; laboratory analyses; Official methods; proximal analysis; starch application